WOMEN PARTICIPATION IN NIGERIAN POLITICS: CHALLENGES AND PROSPECTS TO NIGERIAN DEMOCRACY - Adamu, Rashida Oyoru (Sanata Dharma University, 2023)
The study examined the extent that Nigerian women contributed to political participation in the country and also the factors that hinder them from participating fully. The issue of women in politics has dominated the political debate since Nigeria gained its independence. Nigerian women have not received the kind of representation that is required to enable them to influence the political space like their male counterparts as this makes it difficult for women to be part of the decision-making process. The study adopted Liberal feminism theory to explain gradual improvements through advocating for equal rights for all, and legislation and policies that promote equality. The study adopted content analysis and the study relied on secondary sources of data. The study revealed that several impediments have been identified that limit the participation of women in politics. These barriers are cultural, economic, and legal amongst others that have affected the participation of women in politics. The study concluded that even though women may function at the greatest levels in both the public and private realms, a vicious loop of barriers frequently hinders their ability to lead. The success of these individuals as leaders has been significantly hampered by both internal and external obstacles, including societal and cultural prejudices, patriarchy, the challenge of juggling parental and professional commitments, and a lack of networking. The study recommended that to gain the necessary leadership qualities, women should choose to pursue positions of leadership in both the public and private sectors and should educate themselves to the highest levels. To reduce illiteracy and prepare female students for future leadership duties, parents, especially those in rural areas, should be urged to enroll their female children in school. The study also recommended that the current women empowerment policy be reviewed to reflect the actual situation and that government should also establish a network of women leaders so that women can share their leadership successes and challenges to inspire other women who aspire to be leaders.